Assessment of Computation Competence and Non-Count Strategy Use in Addition and Subtraction in Grade 1 - Delia Leuenberger; Elisabeth Moser Opitz; Noemi Gloor (Journal of Numerical Cognition)
Computation competence (CC) in simple addition and subtraction using non-counting (NC) strategies is an important learning objective in Grade 1 mathematics but many children, especially low achievers in mathematics, struggle to acquire these skills. To provide these students with the support they need, it is important to have valid and reliable tools for assessing progress in CC and NC strategy use. Developing an assessment instrument for use in Grade 1, when some children start the year unable to solve any problems, is challenging, as is ensuring measurement invariance over a school year when children generally make large achievement gains. This paper presents a new assessment tool for CC and NC strategy use in Grade 1 that was tested in a longitudinal study with N = 1,017 children. Analyses using the Rasch model revealed acceptable mean square scores (MNSQ 0.83 – 1.20). Warm’s Weighted Likelihood Estimate (WLE) reliability scores were acceptable (pre-test .77; post-test .87). Measurement invariance over time was given. The instrument is promising for assessing CC and NC strategy use efficiently and accurately in Grade 1.